Expressão recombinante e caracterização de uma endoxilanase não descrita de Trichoderma harzianum - Generoso, Wesley Cardoso (2012)
The use of alternative and renewable fuels is vital to solve the problems derived from the dependence of fuels, and the vegetal biomass is the only renewable source available in large scale that can be converted in energy. The bioethanol production has demonstrated a huge potential to minimize the environmental changes resultant from fossil fuels consumption. Nevertheless, the production costs of cellulolytic complexes lays out one of the major obstacle of the economical viability of the second generation ethanol. Therefore, the bioprospection and the understanding of enzymes involved in the process can improve the complexes productivity. Xylanases are enzymes used in several biotechnological processes, primordially for biopulping and biobleaching in papel industries. However, current surveys have investigated these enzymes due to an accessory role for bioethanol production. In this study, an endoxylanase (xyn3) gene from Trichoderma harzianum was cloned into Pichia pastoris. The constitutive vector pGAPZαA was used, changing the α-factor by the native signal peptide of the enzyme, and with a 6xHisTag at C-terminus. The recombinant protein were expressed in two majority forms, one with a molecular mass of 35 kDa (non-glycosylated) and the other with 60 kDa (glycosylated). Both forms showed xylanolytic activity in zymogram and were biochemically analyzed. The enzymes present optimal temperature of 40°C and pH 6.5, and stable activity until 30°C. The glycosylation plays important role in the enzymatic kinects of the recombinant enzyme, showing a catalytic efficiency twice higher of glycosylated form, in comparison with the activity of the non-glycosylated form. Even in this study, the effects of cellulose and xylan on the regulation of expression of the xyn2, xyn3 and egl3 genes were investigated to T. harzianum. All studied genes were overexpressed under all induction conditions and the results indicate a higher and earlier expression of these genes in fungus induction using a mixture of cellulose and xylan. Furthermore, an advance in the period of induction was observed while the fungus was cultivated with steam explosed bagasse supplemented with endoxylanase 3, when compared with the pure bagasse utilization. These findings enhance the vii understanding of enzymatic mode of action involved in deconstruction of plant cellular wall, whick can be used in the second generation ethanol production.